2017
DOI: 10.3390/f8090322
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Forest Canopy and Surface Fuels from Lidar and Satellite Time Series Data in a Bark Beetle-Affected Forest

Abstract: Wildfire behavior depends on the type, quantity, and condition of fuels, and the effect that bark beetle outbreaks have on fuels is a topic of current research and debate. Remote sensing can provide estimates of fuels across landscapes, although few studies have estimated surface fuels from remote sensing data. Here we predicted and mapped field-measured canopy and surface fuels from light detection and ranging (lidar) and Landsat time series explanatory variables via random forest (RF) modeling across a conif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 104 publications
(115 reference statements)
3
35
0
Order By: Relevance
“…This result was expected, due to the inability of optical sensors to penetrate the forest canopy [67], limiting their use for estimating surface fuel characteristics where tree canopies are present [12]. Similar goodness-of-fit statistics have been reported for other authors; for example, Jin and Chen [19] fitted linear models to estimate loads of different time-lag fuels, with percentages of variance explained ranging from 6% to 17% using Landsat TM data, and from 3% to 45% using high spatial resolution QuickBird data; Bright et al [77] reported percentages of variance explained ranging from 16% to 30% for different time-lag fuels in a coniferous montane forest in Colorado, US, using Random Forest and LiDAR-derived metrics. These percentages increased by 2-8% when Landsat time series variables were added to the model.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This result was expected, due to the inability of optical sensors to penetrate the forest canopy [67], limiting their use for estimating surface fuel characteristics where tree canopies are present [12]. Similar goodness-of-fit statistics have been reported for other authors; for example, Jin and Chen [19] fitted linear models to estimate loads of different time-lag fuels, with percentages of variance explained ranging from 6% to 17% using Landsat TM data, and from 3% to 45% using high spatial resolution QuickBird data; Bright et al [77] reported percentages of variance explained ranging from 16% to 30% for different time-lag fuels in a coniferous montane forest in Colorado, US, using Random Forest and LiDAR-derived metrics. These percentages increased by 2-8% when Landsat time series variables were added to the model.…”
Section: Discussionsupporting
confidence: 59%
“…Pierce et al [14] reported values of 8% and 63% of observed CBH and CBD variance explained with RF models using Landsat 5 TM data and topographic features in conifer forests of north California, US. Bright et al [77], in a study of a coniferous montane forest in Colorado, US, obtained values of 28% and 46% of variance explained for CBH and CBD, respectively, with RF models and LiDAR-derived metrics. Falkowski et al [16] explained 47% of CBD-observed variance with linear models using ASTER images in a mixed temperate conifer forest in Idaho, USA.…”
Section: Discussionmentioning
confidence: 99%
“…Of the original 55 predictor variables, only one, describing the proportion of returns between 5 and 10 m (STRATUM5), was retained across all models. This finding is consistent with previous studies that have previously identified canopy strata return proportions as important across multiple models of forest attributes [79,80]. For the models of CFBH and LCBH, the most important variables are identical (LMOM1, STRATUM6).…”
Section: Discussionsupporting
confidence: 91%
“…It is confirmed in the work of more experts, e.g. Bright et al (2017); Crespo-Peremarch, Ruiz, and Balaguer-Beser (2016), and Chen, Zhu, Yebra, Harris, and Tapper (2016).…”
Section: Introductionmentioning
confidence: 70%